The Organizational Culture of the Khalafiyah Islamic Boarding School in Batanghari Regency in Providing Job Satisfaction for Teachers - Ahmad Hariandi; Hasbi Umar; Kasful Anwar Us (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
The purpose of this research is to learn about the organizational culture and job satisfaction at the khalafiyah Islamic boarding school, as well as to discover whether organizational culture can provide job satisfaction for the teachers at the khalafiyah Islamic boarding school in Batanghari Regency. A qualitative research methodology was applied in this study. Three Islamic Boarding Schools in Batanghari Regency served as research subjects. Documents, records, archives, or printed news are examples of data sources. Passive participatory observation, in-depth interviews, and documentation studies were employed as data gathering methods. Based on the study's findings, it is possible to conclude that the cultures that exist at the three Islamic boarding schools have distinct characteristics and have evolved into a culture that is formed, believed, guided, and acted upon. Based on the study's findings, it can be concluded that the cultures that exist in the three Islamic boarding schools have distinct characteristics and become a culture that is created, believed, guided, and actualized as rules that must be obeyed in order to limit behavior (self-control) and make it a tradition and personality.